Predictive Effects of Knowledge, skills, Understanding and Attitude on Graduate Employability in South West, Nigeria - Fehintola, Joseph O. (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
This study is designed to establish the relationship, composite and relative effects of knowledge, skills, understanding and attitude on graduate employability in south-west, Nigeria. Descriptive research design of correlational type was employed to investigate the relationship that exists between the independent variables and dependent variable. The employers of university graduates in south west, Nigeria were used. 518 participants out of which 422 are males and the rest 95 are females were involved in study. Secondary data were collected and used for the study using the information from the APAFORM (Annual Performance Form) of the concerned university graduates records file. Correlation and multiple regression analysis were used to analyze the three research questions that were raised at 0.05 levels of significances. The result revealed significant correlation, composite effect and relative contributions with skills as the most potent predictor (B = 0.416, t= 7.924, p < 0.05) followed by attitude (B = 0.319, t = 4.194, p < 0.05) followed by knowledge (B = 0.207, t = 4.373, p < 0.05) and finally followed by understanding (B = 0.183, t= 3.319, p < 0.05) in that order. Based on the findings of this study, it was recommended that skills acquisition of university graduates is very important for employability and to retain the job gained. Also, that curriculum planner should lay emphasis on practical aspect of each profession during teaching-learning exercise. Also, that both formative and summative assessment of the learners should be properly done so as to showcase those that are capable in theory, practical and both theory and practical simultaneously in each professional programme so as to help the employers to put round pegs into round holes as the case may be. Keywords: Knowledge, Skills, Understanding, Attitude, Graduate, Employability